Effect of substrate type on fecundity and Nauplii production of ablated Penaeus monodon Fabricius - Pudadera, Rosario A.; Primavera, Jurgenne H.; Borlongan, Emeterio (1980)
The survival, spawning, fecundity, and nauplii production of ablated Penaeus monodon females reared in flow-through broodstock tanks with white coralline and black sand substrates for 62 days, were assessed. Prawns exposed to the white coralline substrate consistently produced eggs with significantly higher (P - 0.05) average hatching rates and total nauplii production than those exposed to the black sand substrate. No differences were observed in the fecundity, spawning and survival rates in both treatments. It was observed that nightly sampling of ablated females during experiment 2 produced a higher number of spawning (48) and total number of nauplii produced (6.8 milion) compared to twice weekly sampling in experiment I (29 spawnings and 3.0 million nauplii) for the white substrate.